2020
DOI: 10.1007/s12250-020-00290-7
|View full text |Cite
|
Sign up to set email alerts
|

Early Serum HBsAg Kinetics as Predictor of HBsAg Loss in Patients with HBeAg-Negative Chronic Hepatitis B after Treatment with Pegylated Interferonα-2a

Abstract: Hepatitis B surface antigen (HBsAg) loss is an ideal treatment endpoint for patients with chronic hepatitis B (CHB). We investigated the predictive value of on-treatment HBsAg levels for HBsAg loss in hepatitis B e antigen (HBeAg)-negative CHB patients who received 120-week PEG-IFNa-2a treatment. Serum HBV DNA, HBsAg, and anti-HBs levels were assayed at baseline and every 3 months during the treatment. Of 81 patients, 12 achieved HBsAg loss, 20 achieved HBsAg \ 100 IU/mL, and 49 maintained HBsAg C 100 IU/mL. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…NA treatment cannot effectively reduce viral antigen, so it is difficult to achieve clinical cure ( 7 ). Interferon can reduce the production of viral antigens and restore the function of damaged immune cells, resulting in a higher HBsAg disappearance rate than NA treatment ( 12 , 13 , 21 , 35 ). Our study showed that the baseline IL-10, IL-6 and TGF-β2 levels were not different in the two groups, but after 24 weeks of interferon treatment, the level of IL-10 in the clinical cure group was significantly lower than that in the non-clinical-cure group, and the clinical cure group had a greater decline range of IL-10 and TGF-β2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NA treatment cannot effectively reduce viral antigen, so it is difficult to achieve clinical cure ( 7 ). Interferon can reduce the production of viral antigens and restore the function of damaged immune cells, resulting in a higher HBsAg disappearance rate than NA treatment ( 12 , 13 , 21 , 35 ). Our study showed that the baseline IL-10, IL-6 and TGF-β2 levels were not different in the two groups, but after 24 weeks of interferon treatment, the level of IL-10 in the clinical cure group was significantly lower than that in the non-clinical-cure group, and the clinical cure group had a greater decline range of IL-10 and TGF-β2.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies found that changes of virological and serological indexes could predict the disappearance of HBsAg in CHB patients treated with interferon ( 10 , 11 ). If patients were given consolidation treatment of interferon for 12-24 weeks after functional cure, it was not easy to relapse ( 10 , 12 , 13 ). We also found that incidence of hepatitis B was positively correlated with IFN-α, and negatively correlated with transforming growth factor-beta (TGF-β) and interleukin- 10 (IL-10) ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our study also shows that in patients treated with nucleoside analogues for viral suppression, a higher rate of surface antigen disappearance can be achieved by combination therapy with interferon [8] . Because of the research which highlighted the importance of extension treatment to the maintenance of HBsAg vanishing in CHB patients [9,10] , we extended the treatment for another 24 weeks after the patient had achieved the disappearance of the surface antigen, in order to better maintain the state of functional healing.…”
Section: Discussionmentioning
confidence: 99%
“…Functional cure occurs at an average annual rate of 0.22% in CHB patients during first-line oral NAs antiviral treatment ( 42 ). PEG-IFN treatment can acquire an average HBsAg clearance annual rate of 3% ( 43 45 ), 5-year cumulative rate of 14% and 10-year cumulative rate of 32% ( 46 ) in CHB patients. But in inactive HBsAg carriers, the HBsAg clearance rate can reach to 47% after 48 weeks of PEG-IFN treatment ( 47 ).…”
Section: Immune Mechanisms Of Current Drugs and Emerging Therapies Ta...mentioning
confidence: 99%